Eagle Station : A Novel - Brown, Dale 1956-; Snow, Corey ([New York, New York] : HarperAudio, 2020)
Brad McLanahan and the Space Force must fight to preserve America's freedom when a pair of ruthless enemies forges an unlikely alliance to control not only the earth, but the moon and beyond.
Keywords: McLanahan, Patrick (Fictitious character) -- Fiction; Space weapons -- Fiction; Special operations (Military science) -- Fiction; Special forces (Military science) -- Fiction; Terrorism -- Fiction -- Prevention; Space stations -- Fiction; National security -- Fiction -- United States; FICTION / Thrillers / Military; FICTION / Thrillers / Political; FICTION / Thrillers / Espionage; Audiobooks; Thrillers (Fiction)